In Search of Smart Specialization to Ensure the Sustainable Development of the Post-Conflict Territory: the Case of the Luhansk Region in Ukraine - Shevtsova, Hanna; Shvets, Nataliia; Kramchaninova, Maiia; Pchelynska, Hanna (European Journal of Sustainable Development, 2020)
This work highlights a range of problems related to ensuring sustainable development of post-conflict territories, as well as ways to overcome those through smart specialization approach. The influence of military conflict on Luhansk region's economy structure and economy's pace of development had been determined. Capacities of smart specialization as a contemporary tool meant for intensifying innovative development, structural modernization and improving competitiveness of regions had been studied. While researching regional context the current state and structure of the chemical sector, which is region's traditional specialty, had been analyzed and also its SWOT analysis had been conducted. Potential for diversification, innovative and cross-sectoral evolution of the existing chemical business was discovered. We pay attention to chemical production's digitalization horizons and its integration into rapidly growing region's agricultural sector as part of precision farming concept. The suggested agrochemical ecosystem's model facilitates communications between leading stakeholders, increases efficiency of entrepreneurial discovery process, creates new areas of specialization and new leverage for ensuring region's sustainable development. Keywords: sustainable development, smart specialization, chemical industry, agriculture, ecosystem, precision farming, Luhansk region